Microwave‐Assisted Multicomponent Reaction: A Green and Catalyst‐Free Method for the Synthesis of Poly‐Functionalized 1, 4‐Dihydropyridines. Issue 32 (27th August 2019) - Maddila, Suresh; Nagaraju, Kerru; Chinnam, Sampath; Jonnalagadda, Sreekantha B
Abstract: A facile and an efficient procedure for the synthesis of poly‐substituted 1, 4‐dihydropyridine derivatives under catalyst‐free conditions has been established by a one‐pot multi‐component reaction in EtOH solvent under microwave irradiation (150 W). The remarkable benefits of this approach are: simple operation, non‐toxic, short reaction time (< 5 min), excellent yields (93‐98%), no column chromatography, clean reaction profile and environmentally friendly reaction. Abstract : A facile and an efficient procedure for the synthesis of poly‐substituted 1, 4‐dihydropyridine derivatives under catalyst‐free conditions has been established by a one‐pot multi‐component reaction in EtOH solvent under microwave irradiation at room temperature. The remarkable benefits of this approach are: simple operation, non‐toxic, short reaction time (< 5 min), excellent yields (93‐98%), no column chromatography, clean reaction profile and environmentally friendly reaction.